The principle of procedural equality in the contentious-administrative labor litigation proceeding. The suitable way of compensation for damages as the sole claim - Seguil Muñoz, Jennifer Jane (2023)
This article analyzes whether the decision adopted by the superior judges in the National Labor and Labor Procedural Jurisdictional Plenary of 2017, regarding the procedural route of the claims for compensation for damages filed by public workers as a sole pretension, violates the principle of procedural equality provided in numeral 5.5 of article 5 of the TUO of the Law of Contentious Administrative Procedure.